The Ethics of Sankara and Santideva: A Selfless Response to an Illusory World, by Warren Lee Todd - Abramson, John (Buddhist Studies Review, 2015)
The Ethics of Sankara and Santideva: A Selfless Response to an Illusory World, by Warren Lee Todd, Ashgate Publishing, 2013. xii + 220pp., Hb. £60.00. ISBN-13: 9781409466819.